Differences of Escherichia coli isolated from different organs of the individual sheep: molecular typing, antibiotics resistance, and biofilm formation - Wu, Zihao; Chi, Haoming; Han, Tingting; Li, Guangxi; Wang, Jixue; Chen, Wei (Folia microbiologica, 2024)
Despite numerous studies on Escherichia coli (E. coli) from sheep, there have been few reports on the characterization of E. coli isolates from various organs of individual sheep until now. The present study conducted molecular typing, antibiotics resistance, biofilm formation, and virulence genes on E. coli isolated from 57 freshly slaughtered apparently healthy sheep carcasses, gallbladders, fecal samples, and mesenteric lymph nodes (MLNs). The results demonstrated that the detection rate of R1 LPS core type in E. coli isolated from fecal samples (70.83%) was higher than that from other organs, but the detection rate of antibiotic resistance genes was lower (P < 0.05). The predominant phylogenetic group of E. coli isolated from the carcasses was group B1 (93.33%), and the detection rate of multidrug-resistance phenotype (80%) and the resistance rate of E. coli was higher than that from other organs (P < 0.05). Interestingly, the intensity of biofilm formation of E. coli isolated from MLNs was higher than that from other organs (P < 0.05). However, except for ibeB, the detection rates of virulence genes did not differ in E.coli isolated from different organs. In conclusion, differences were noted in these parameters of E. coli isolated from different organs of individual sheep. Therefore, the data may contain considerable mistakes concerning the actual situation in the host if we only analyze the data of E. coli isolated from feces or carcasses.
Keywords: Virulence; Animals; Individual sheep; Virulence Factors; Molecular Typing; Escherichia coli Infections; Feces; feces; infekce vyvolané Escherichia coli; Escherichia coli; ovce; Anti-Bacterial Agents; molekulární typizace; bakteriální léková rezistence; virulence; Phylogeny; Biofilm formation; Different organs; nemoci ovcí; Sheep; Molecular typing; Antibiotics resistance; biofilmy; zvířata; antibakteriální látky; fylogeneze; Drug Resistance, Bacterial; Biofilms; faktory virulence; Sheep Diseases